Increasing Children's Sense of Responsibility Through Poster Comment Media Group B - Megawati Edy; Khairul Huda; Hernawati (Jurnal Pengetahuan dan Pendidikan, 2024)
This research focuses on how rights, obligations and compliance with rules reflect children's responsibilities at school. Where this still really needs to be improved. There are still many children in group B of Raudhatul Jannah IT Kindergarten who have low levels of responsibility, even in the summative assessment of learning themes that contain this aspect, less than 50% of children are able to achieve it. Children still need to increase their motivation because children's motivation to be responsible is still very low, disregard for rules is often shown and other things related to a sense of responsibility. This research is PTK research with 2 implementation cycles, namely cycles I and II. The subjects of this research were 11 children. The data collection method is observation. From the results of the analysis of research data, it can be concluded that aspects of social-emotional development (children's sense of responsibility) can be improved through the creation of poster comment media with guided discussions for Group B children of Raudhatul Jannah IT Kindergarten. The results of research in cycle I showed that as many as 63% (7) children had not yet completed or were still in the T.T.KKM / BB (Not Yet Developing) and MB (Starting to Develop) criteria and as many as 36% (4) children had completed or were on the Ter.KKM / BSH (Developing According to Expectations) and BSB (Very Well Developing) criteria. Meanwhile, an increase occurred in cycle II where as many as 91% (10) children completed or were already at the Ter.KKM / BSH (Developing According to Expectations) and BSB (Very Well Developing) criteria. As many as 8% (1) of children have not completed or are still in the T.T.KKM category